National teaching awards and the pursuit of teaching excellence - Israel, M.; Bennett, Dawn (Routledge, 2018)
Mark Israel and Dawn Bennett examine national teaching awards implemented in the UK, Australia, New Zealand and Canada. They question how much influence such awards have in terms of acting as agents of institutional change, and go further to suggest that institutions themselves do not really value, or take seriously, such schemes. Indeed, there is limited evidence to suggest they have much impact on awardees, teaching quality or students’ learning. In concluding, Israel and Bennett assert that in order for national teaching awards to impact purposefully on excellence, they need to support awardees to work alongside others, encourage organizational alignment with institutional missions, and give awarding bodies the authority to empower awardees to make a significant contribution to the sector.